HUBUNGAN VOLUME, KECEPATAN DAN KEPADATAN LALU LINTAS PADA RUAS JALAN PADJAJARAN (RING ROAD UTARA), SLEMAN - Grisela Nurinda Abdi; Sigit Priyanto; Siti Malkamah (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2019)
A macroscopic movement of traffic consists of traffic volume, speed and density which are used to evaluate the quality of transportation system. By analysing these three variables, a result which infrom about the condition about a transportation system will be provided. The information from the analysis of the variables shows the condition of the traffic condition through the traffic volume and density. When a road has a bad condition of transportation system, the analysis will describe it through high density of traffic and the maximum traffic volume is exceeded.This research is conducted on Padjajaran Street to evaluate the characteristic of transporatation system on the road.The data, which were collected, consists of traffic volume and spot-speed on every lane of the road. Those were collected on Monday, Wednesday, Saturday and Sunday at peak-hours, which are 6.30am-8.30am, 11am-1pm and 4pm-6pm. The analysis used vehicles classification according to MKJI 1997 and conducted an analysis through several models, which are Greenshield, Greenberg, Underwood and Bell models. By comparing these four models, the best one is chosen and become the model to describe the quality of the transportation system on Padjajaran Street.The best result according to the value of R2 and the analysis of the traffic variables, every lane has their own best model which can be applied. However, most of the lanes are well-modelled using Underwood method. Finally, it comes to a conclusion that Padjajaran Street is classified as urban road.